Study on the mechanism of family resilience on loneliness in older adults with stroke - Ju, Hui; Dong, Yanli; Liu, Ju; Mu, Jing; Ge, Lei; Chen, Jie (Frontiers in Psychology, 2025)
ObjectiveThis study examines loneliness in stroke patients who were ≥60 years of age, identifying key factors such as family resilience, social support, family function, and psychological capital.MethodsWe sampled 234 stroke patients who were ≥60 years of age. These patients were diagnosed with stroke (ischemic stroke, hemorrhagic stroke) by the hospital and their condition is stable in the recovery period. Data were collected using the UCLA Loneliness Scale, Family Resilience Assessment scale, Positive Psychological Capital scale, Family APGAR Index, and Social Support Rating Scale. Using one-way analysis of variance and multiple linear regression equation to analyze the influencing factors of loneliness in older adults with stroke; Construct a structural equation model to explore the pathways of social support, family function and psychological capital in the relationship between family resilience and loneliness.ResultsThe average loneliness score among older adults with stroke was (35.07 ± 15.24). Factors affecting loneliness included income, activity level, community resources, social participation, and illness duration. Pearson analysis showed significant negative correlations between loneliness and family resilience (r = −0.738, P < 0.01), social support (r = −0.715, P < 0.01), family function (r = −0.745, P < 0.01), and psychological capital (r = −0.684, P < 0.01). Family resilience has a direct negative predictive effect on loneliness (β = −0.342, P < 0.001). Social support, family functioning, and psychological capital play a chain mediating effect between family resilience and loneliness, with a mediating effect value of −0.436, accounting for 56.04% of the total effect.ConclusionLoneliness in elderly stroke patients is moderate. Strengthening family resilience and support systems can effectively reduce loneliness.